Determination of Resultant Forces for 2D Hyperstatic Frames using Android-Based Frame Design Application and Finite Element Analysis - Hasibuan, Samsul A Rahman Sidik; Prayuda, Hakas (LPPM Universitas Andalas, 2023)
The slope deflection method assumes all joints are considered rigid, which means the angle does not change under any loads. This ensures that compatibility and deflection are neglected due to shear and axial stress. The numerical determination of forces and deformation in structures through applying the slope deflection method necessitates a relatively extended computational time and demands high-precision results. An effective tool can efficiently and precisely determine internal forces and structural deformations. This study utilizes the Frame Design Application version 5177, initially released on 24 June 2012 and has since been updated as of 2 February 2022, an Android-based application. Utilizing the Frame Design Application facilitates the expeditious and precise determination of internal forces and structural deformations. It is a valuable tool for professionals in civil engineering, mechanical engineering, and architecture, as well as students seeking to build 2D hyperstatic frames through Finite Element Analysis (FEA). The primary objective of this paper is to evaluate the precision of the Frame Design Application to determine its suitability for educational purposes. This paper will also evaluate the precision of the analysis outcomes by manual calculations and the utilization of SAP2000 Software. The provided analysis results exhibit negligible disparities. The Frame Design Application is a highly recommended tool for those in civil engineering, mechanical engineering, architecture and students seeking to design 2D hyperstatic frames through Finite Element Analysis (FEA).